(untitled) (Nexo Revista Científica, 2022)
Carbon bonds are a management tool that is being implemented globally to reduce CO2 emissions into the environment, through forest, soil and water conservation protocols. It forms a main part of the commitments made in the Kyoto Protocol to reduce global warming. For its part, the state of Quintana Roo is a pioneer in the incursion of carbon bonds at the micro-basin level, and where sustainable tourism is consolidated as a preponderant activity catapulted by the spill over effect of the Mayan Train Megaproject, however; the lack or inadequate environmental planning could produce deleterious effects. In this sense, they have been allocated by assembly agreement in 2019 (35 thousand Ha) of tropical forest as ANP. With the technical support of specialists (UTCalakmul), the total biomass, carbon storage and fixation in PF and SAF were estimated as a mitigation indicator according to IPCC. Total height and DBH of trees with DBH≥10 cm and D30 in the case of timber trees were measured. BA was estimated using allometric methods and with biomass expansion factors. The average fixation rate was 5.9 t C/ha/year and the FPs stored up to 70 t C/ha. The participation of the ejido in caring for the forest, soil and water in collaboration with NGOs led to the issuance of the bonds as of August 15, 2021. The results obtained demonstrate the importance of these mechanisms for the promotion of soil, water and forest conservation in Quintana. Roo. And that the integral participation in community projects by academics, NGOs and community members is viable and feasible.